INTERNATIONAL EXPERIENCE AND MECHANISMS FOR IMPLEMENTING LANGUAGE POLICY IN NATIONAL EDUCATION SYSTEMS - Lola Tilavmurodova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Language policy in national education systems plays a crucial role in preserving cultural identity, promoting social inclusion, and supporting effective teaching. Another important aspect of language policy today is that multilingualism is considered a key factor not only for young people but for society as a whole. The effective promotion of language policy contributes to the introduction of new opportunities and conveniences. As a result, linguistic richness increases and attracts the interest of speakers of other languages.International experience shows that successful language policy balances the development of the national language with multilingual education and respect for linguistic diversity. Different countries implement various mechanisms such as bilingual curricula, teacher training, and inclusive language standards to ensure equal access to education. From a humanistic perspective, language policy in education should take into account students’ cultural backgrounds, promote mutual understanding, and support the holistic development of the individual. Such approaches contribute to strengthening national unity and enhancing global communication.